SARM1 Ablation Is Protective and Preserves Spatial Vision in an In Vivo Mouse Model of Retinal Ganglion Cell Degeneration - Carty, Michael; Farrar, Gwyneth; Bowie, Andrew (My University, 2022)
The challenge of developing gene therapies for genetic forms of blindness is heightened by the heterogeneity of these conditions. However, mechanistic commonalities indicate key pathways that may be targeted in a gene-independent approach. Mitochondrial dysfunction and axon degeneration are common features of many neurodegenerative conditions including retinal degenerations. Here we explore the neuroprotective effect afforded by the absence of sterile alpha and Toll/interleukin-1 receptor motif-containing 1 (SARM1), a prodegenerative NADase, in a rotenoneinduced mouse model of retinal ganglion cell loss and visual dysfunction. Sarm1 knockout mice retain visual function after rotenone insult, displaying preservation of photopic negative response following rotenone treatment in addition to significantly higher optokinetic response measurements than wild type mice following rotenone. Protection of spatial vision is sustained over time in both sexes and is accompanied by increased RGC survival and additionally preservation of axonal density in optic nerves of Sarm1−/− mice insulted with rotenone. Primary fibroblasts extracted from Sarm1−/− mice demonstrate an increased oxygen consumption rate relative to those from wild type mice, with significantly higher basal, maximal and spare respiratory capacity. Collectively, our data indicate that Sarm1 ablation increases mitochondrial bioenergetics and confers histological and functional protection in vivo in the mouse retina against mitochondrial dysfunction, a hallmark of many neurodegenerative conditions including a variety of ocular disorders.
PUBLISHED
Keywords: Axon degeneration; Retinal degeneration; Sterile alpha and Toll/interleukin-1 receptor motif-containing 1 (SARM1); NADase; NAD+